Complete mitochondrial genome of Manchurian Zokor (Myospalax psilurus). (3rd March 2016) - Li, Yangwei; Lu, Jiqi; Wang, Zhenlong
Abstract: Manchurian Zokor ( Myospalax psilurus ) is a common subterranean rodents which have a wide distribution in Transbaikalia, east Mongolia, east and central China, and Far East of Russian. The complete mitochondrial (MT) genome of M. psilurus has been determined in this study. It is a 16 360 bp circular molecule containing 13 protein-coding, 22 tRNAs and 2 rRNAs genes. Except for the seven tRNA and Nd6 genes, all other mitogenes are encoded on the heavy strand. The overall nucleotide composition of the H-strand is 33.68% A, 28.77% T, 25.35% C, and 12.17% G. Total A + T content is 54.12%.